James Patterson by James Patterson: The Stories of My Life - Patterson, James, 1947- (New York : Little, Brown and Company, 2022)
A #1 bestselling author shows how a boy from small-town New York made it to literary stardom.
Keywords: Patterson, James, -- 1947-; Authors, American -- Biography; Autobiographies